Charge-coupled device based on optical tomography system for monitoring two-phase flow - Jamaludin J.; Rahim R.A.; Rahim H.A.; Rahiman M.H.F.; Rohani J.M. (Institution of Engineering and Technology, 2024)
Electronics LettersVolume 53, Issue 5 p. 331-333